BETWEEN ART AND FAITH: EXPLORING SPIRITUAL EXPRESSIONS IN CONTEMPORARY MUSLIM ART - Nur Anna, Dian; Maryono (UIN Antasari Banjarmasin, 2025)
This research explores the spiritual expressions of Muslim artists in contemporary paintings. In this era, Muslim artists often pursue art for art's sake, influenced by their background and spirituality. Though these are not always visible, they embed Islamic values into their work. The study uses a qualitative approach, analyzing data through Sayyed Hossein Nasr's spirituality theory and Kuntowijoyo. Findings show that Muslim artists, especially in Yogyakarta, expand their expertise to create appreciated works. About 28.57% focus on religious themes, 28.57% depict the universe, humanity, and religion, and 28.57% focus on the universe and humanity. Artists create with spiritual awareness, guided by their abilities. Those with higher education tend to be more deliberate in their choices. In Yogyakarta, 85.71% is for livelihood, 100% for artistic expression, and 28.57% for socio-political purposes. Driven by various motivations, Muslim artists contribute to society. The government, society, and art figures can collaborate toward a just, prosperous society.